2020
DOI: 10.3390/polym12020346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eleview® Bioadhesive Properties and Cushion-Forming Ability

Abstract: Submucosal injection is generally required for both endoscopic-mucosal resection (EMR) and submucosal dissection (ESD). SIC-8000 (Eleview®) is a new liquid composition in the form of a microemulsion for submucosal injection, approved by the Food and Drug Administration (FDA) 510(k) and Conformité Européene (CE) marked, containing a biocompatible polymer as a cushioning agent. The aim of this study was to evaluate Eleview®’s performance in terms of bioadhesive properties and cushion-forming ability. The bioadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…(2) more importantly, the described behaviour of the polyps after the submucosal injection of both Eleview and EverLift lack (a) the elevation of the other submerged polyps in the proximity of injection and (b) volume changes of the polyp itself. Interestingly in the paper comparing the Eleview vs HES contrasting composition authors did not notice the volume change of polyps themselves, focusing rather on bolus volume dynamics 5 . While the elevation time of Eleview is excellent, the differences in volume changes lead us to believe, that the EMR solution activity based on HES is on first sight similar but acts on different mechanism.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2) more importantly, the described behaviour of the polyps after the submucosal injection of both Eleview and EverLift lack (a) the elevation of the other submerged polyps in the proximity of injection and (b) volume changes of the polyp itself. Interestingly in the paper comparing the Eleview vs HES contrasting composition authors did not notice the volume change of polyps themselves, focusing rather on bolus volume dynamics 5 . While the elevation time of Eleview is excellent, the differences in volume changes lead us to believe, that the EMR solution activity based on HES is on first sight similar but acts on different mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…The physiological solution with the addition of methylene blue or sodium salt of indigotindisulfonate was applied as a visual tool to stain the neoplasm 4 . Only very recently, the ready-made injection solutions Eleview and EverLift were introduced on some markets 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparative trial found that eleview injections significantly increased the height and duration of mucosal lift compared with saline injections, creating a buffer layer for polyp removal surgery and improving the success rate of surgery. Therefore, eleview is expected to be an effective alternative to saline injection ( 40 ). The keyword “cold snare polypectomy” exploded in 2017, and the use of cold snares to ligate tumors or polyps is becoming a popular research topic.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been done on viscous solutions and there are now several high-viscosity products available, such as hyaluronic acid 10 or poloxamers, which offer interesting properties of variable viscosity according to temperature 11 12 13 . These products are efficient but expensive.…”
Section: Submucosal Injectionmentioning
confidence: 99%